2016
DOI: 10.1371/journal.pone.0148911
|View full text |Cite
|
Sign up to set email alerts
|

SULF2 Expression Is a Potential Diagnostic and Prognostic Marker in Lung Cancer

Abstract: AimsLung cancer is one of the most deadly cancers; median survival from diagnosis is less than one year in those with advanced disease. Novel lung cancer biomarkers are desperately needed. In this study, we evaluated SULF2 expression by immunohistochemistry and its association with overall survival in a cohort of patients with non-small cell lung cancer (NSCLC). We also looked for the presence of SULF2 protein in plasma to evaluate its potential as an early detection biomarker for NSCLC.MethodsWe identified pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Lung cancer is a leading cause of cancer-associated death and epigenetic dysregulation of numerous signaling pathways are involved in. 31 Abnormal activation of AKT has been considered as a frequent event in lung cancer cells. 32 Likewise, the activation of the JAK/STAT3 pathway, which is required for TGF-β-induced EMT, is also frequently observed in human lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is a leading cause of cancer-associated death and epigenetic dysregulation of numerous signaling pathways are involved in. 31 Abnormal activation of AKT has been considered as a frequent event in lung cancer cells. 32 Likewise, the activation of the JAK/STAT3 pathway, which is required for TGF-β-induced EMT, is also frequently observed in human lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by using biochemical and imaging approaches, we found that TRF2 regulates the extracellular release of VEGF-A, altering the equilibrium between cell-free and cell-associated amount of VEGF-A. This property of TRF2 is dependent on the expression of SULF2, a sulfotransferase with a potential oncogenic role that has been found overexpressed in subsets of multiple tumors (56). This enzyme, indeed, inducing post-synthetic modification of HSPGs, is capable of modulating the extracellular release of a number of growth factors containing an heparin-binding domain, including VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from an investigation on liver cancer suggested that overexpressed SULF2 predicted a worse prognosis (25). In addition, SULF2 expression might be credited as a valuable diagnostic and prognostic biomarker in non-small cell lung cancer (26). Furthermore, Flowers et al (27) found that increased SULF2 expression was positively related to the clinical stage of head and neck squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%